Trehalose as a potential therapeutic agent in different diseases - Stevanović Danijela; Trajković Vladimir; Vučićević Ljubica (Medicinski Podmladak, 2023)
Trehalose is a natural, non-reducing disaccharide synthesized in some bacteria, fungi, plants, and insects. Due to its advantageous physical and chemical properties, trehalose can stabilize proteins and membranes, and protect cells from desiccation, heating, and freezing. Vertebrates do not synthesize trehalose, but the beneficial effects of trehalose have been demonstrated in numerous diseases as it eliminates aggregates, misfolded proteins, and damaged organelles, and reduces hyperinflammation and oxidative stress. Trehalose induces autophagy through nuclear translocation and activation of transcription factor EB (TFEB) in an mTOR-independent manner, but increases the expression of SQSTM1/p62 and has antioxidant properties in an autophagy-independent manner. Furthermore, trehalose induces apoptosis in tumor cells by increasing membrane fluidity through the activation of caspase 3, 6 and the JNK (c-Jun N-terminal kinase) pathway. Overall, in this review, previous knowledge on the therapeutic potential of trehalose in various diseases such as dry eye syndrome, neurodegenerative diseases, and tumors, was summarized, focusing on the underlying molecular mechanisms.